DIFFERENCES IN THE EFFECT OF EXERCISE ON SKIPPING PLYOMETRICS AND POWER ON LEG MUSCLES BASKETBALL PLAYERS - RAHMAT IQBAL; WENDI GUSHENDRA (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2016)
This research is an experimental research aims to determine differences in the effects of exercise plyometrics and skipping the leg muscle power in Padang Panjang basketball player. The hypothesis of this study is: 1) There is the effect of exercise plyometrics to power leg muscle. 2) There is the effect of skipping exercise on limb muscle power. 3) There are differences in the effects of exercise plyometrics and skipping the leg muscle power on basketball players. The population is player basketball club Galaxy Padang Panjang numbered 20 athletes of male, because of the limited number of existing populations, then the entire population sampled (total sampling). After the pre-test all samples were divided into two groups with a total of ordinaly pairing techniques. Both groups consisted of a group of plyometrics exercises and skipping exercise group. Each group consisted of 10 people. Implementation of the study consisted of 18 sessions, a week exercise held 3 times. The duration of the exercises in each meeting is 90 minutes. The results of the pre test-post test that recorded the ability of leg muscle power of basketball players. Based on data analysis can be concluded that: 1) There plyometrics exercises significant influence on that limb muscle power than the average 72.10 (pre-test) to 78.10 in post test where t = 5.57> table = 2.26. 2) There is a significant effect of skipping exercise the leg muscle power is on average 71.20 (pre-test) to 76.90 in post test where t = 4.36> table = 2.26. 3) There is no difference in the effects of exercise plyometrics and skipping to the power of leg muscle that is on average 78.80 post test and 76.90 post test where t = 1.21 <table = 2.26. Thus the first and second hypothesis is accepted while the third hypothesis is rejected.